Growing up abroad: Italian and Romanian migrants' partial transitions to adulthood. Issue 9 (4th July 2019) - Moroşanu, Laura; Bulat, Alexandra; Mazzilli, Caterina; King, Russell
ABSTRACT: Drawing on in-depth interviews with young Italians and Romanians, representing two of the largest "old" and "new" European populations in Britain, this paper examines migrants' experiences in the spheres of work, family and "home", and their narratives of "growing up" abroad, to enhance our understanding of youth transitions to adulthood in the context of intra-EU migration. Contrary to accounts that see migration as a strategy to either delay or advance adulthood, our analysis offers a more complex picture, showing how migration may unevenly affect transitions to adulthood, advancing some, and delaying others. Furthermore, we extend debates around the meaning of adulthood, illustrating the central role migration plays in generating feelings of "growing up", even when traditional markers of adulthood are absent, and how these are negotiated transnationally in relation to home-based peers, in ways that combine old and new understandings of adulthood.